Efeito da oxigenação hiperbárica no reparo ósseo de ratos diabéticos - Dias, Pâmella Coelho (2016)
The chronic state of hyperglycemia due to diabetes mellitus affects multiples organs impairing life quality. In bone, diabetes alters strength and mineral density and also suppresses the osteoblast activity, leading to an unbalanced bone healing process. Hyperbaric oxygen therapy (HBO) is suggested as an adjuvant treatment to accelerate bone repair. This study evaluated the effects of HBO in the number of mast cells and in new bone formation at the initial stage of bone repair in normoglycemic and diabetic rats. It was hypothesized that HBO treatment may improve bone repair in diabetic bone. The rats were equally divided in four groups: Control (C); Control + HBO (CH); Diabetes (D) and Diabetes + HBO (DH). Diabetes was induced by streptozotocin (65mg/kg) and femoral bone defects were created thirty days after diabetes induction in all groups. HBO initiated immediately after surgery procedure and was performed daily, for 7 days, in the CH e DH groups. Seven days after surgery, all animals were euthanized. The femur diaphyses were removed, fixated, decalcified and processed for paraffin embedding. The semi-serial histological sections obtained were stained with Hematoxylin-Eosin (HE), Mallory Trichrome and Toluidine Blue. The qualitative analysis was conducted in the histology slides stained with HE, where it was evaluated the morphological aspects of bone repair in the lesion area, observing the presence of clot, inflammatory cells, granulation tissue, type of bone tissue, morphology of bone cells, and thickness and organization of bone trabeculae. In the slides stained with Mallory Trichrome and Toluidine Blue were evaluated the percentage of new bone formation and number of mast cells, respectively. The qualitative analysis showed that the CH group presented a more advanced stage of bone repair compared to the C group, showing thicker trabeculae and greater bone filling of the lesion area. In D and DH group, the lesion area was partially filled with new bone formation tissue and presented thinner trabeculae and fewer areas associated to osteoclasts compared to control group. The histomorphometric analysis showed a significant improvement in new bone formation (p<0.001) comparing CH (38.08 ± 4.05) and C (32.05 ± 5.51); C and D (24.62 ± 2.28 and CH and DH (27.14 ± 4.21) groups. In the normoglycemic rats there was a significant increasing in the number of mast cells (p<0.05) comparing C (8.06 ± 5.15) and CH (21.06 ± 4.91) groups. In conclusion, this study showed that diabetes impaired bone repair and HBO was only able to increase new bone formation and the number of mast cells in the normoglycemic animals.